The Role of Knowledge Management Processes in Green Marketing Innovation (A Case Study of Bio Gar Company for Medical and Cosmetic Industries) (Journal of Hama University, 2026)
ABSTRACTThe research aimed to determine the level of application of knowledge management processes and green marketing innovation in the company (BioGar), and to determine the role of knowledge management processes (knowledge generation process, knowledge storage process, knowledge distribution process, and knowledge application process) in green marketing innovation in the company studied. The research relied on the descriptive analytical approach as a general research method, as a questionnaire was designed and distributed to a random sample of workers at the senior, middle, and executive levels in the company studied, and the number of questionnaires valid for statistical analysis was 273 questionnaires. The research concluded that the studied company applies knowledge management processes to a moderate degree, and it also applies green marketing innovation to a moderate degree. The research results indicated that there is a positive moral impact of knowledge management processes on the green marketing innovation process of the studied company. The ranking of knowledge management processes in terms of the severity of the impact on the green marketing innovation process in the studied company was as follows: the process of applying knowledge, the process of storing knowledge, the process of distributing knowledge, and the process of generating knowledge.
Keywords: Keywords: knowledge management, knowledge management processes, green marketing innovation.